Factors Influencing Lack of Interest in the Academic Activities Among Grade-8 Students: A Case Study of Govt. Elementary School RMK-1, District Bhakkar - Muhammad Shahbaz (JCTE, 2026)
This study intends to explore the factors influencing lack of interest in academic activities among grade-8 students. It specifically inquires the elements that make eighth-grade male students at Government Elementary School RMK-1 less likely to be interested in educational activities. The research study examines five key areas through a questionnaire; interpersonal teaching, environmental, sociocultural and psychological factors. A sample size of 19 male students take part in the study where correlation analysis was performed. The study results explain that the instructional component (r =-0.64) have the greatest negative relationship, meaning that successful teaching practices could contribute enormously to the elimination of educational disinterest. The psychological factors (r=0.52) imply a positive correlation, which means that stress, anxiety, and self-esteem problems result in having a disengagement. There was also the role of interpersonal (r= -0.50), environmental (r=-0.47), and sociocultural (r=-0.33) factors but to varying degrees. The research indicates a requirement of enhanced teaching methods, additional student assistance programs, as well as stress management inducing interventions so as to create learning interest in the students.